PERSEPSI DAN MOTIVASI MAHASISWA PENDIDIKAN BAHASA JEPANG TERHADAP PEMILIHAN JURUSAN (STUDI KASUS MAHASISWA PENDIDIKAN BAHASA JEPANG) - Muhammad Iqbal Habib; Merri Silvia Basri; Yenny Aristia Nasution (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the perception and motivation of students in choosing the Japanese Language Education Study Program at Riau University. In addition, it is also to find out the most dominant factors that affect the perception and motivation of students.The method used in this study is the Quantitative Descriptive method by using the Google Docs application as a data retrieval medium, namely Angket. Then the researcher analyzes the data by using the SPSS application to get the mean value. After the mean value is obtained, the calculation of the dominant factor that affects the perception and motivation of students is carried out. The students who were used as respondents were students of the class of 2020, 2021 and 2022.From the results of the study, it can be concluded that students of the Japanese Language Education Study Program have a positive perception and motivation towards the simultaneous selection of their study program. Furthermore, researchers are expected to expand the scope of respondents, not only students in one study program, but also other study programs in the language and arts education department of Riau University.Key Words: Perception, Motivation, Student